2022
DOI: 10.7554/elife.72136
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of distributed working memory in a large-scale network of macaque neocortex

Abstract: Neural activity underlying working memory is not a local phenomenon but distributed across multiple brain regions. To elucidate the circuit mechanism of such distributed activity, we developed an anatomically constrained computational model of large-scale macaque cortex. We found that mnemonic internal states may emerge from inter-areal reverberation, even in a regime where none of the isolated areas is capable of generating self-sustained activity. The mnemonic activity pattern along the cortical hierarchy in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
106
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(114 citation statements)
references
References 101 publications
(189 reference statements)
7
106
1
Order By: Relevance
“…To reproduce these latter experimental activity patterns, we found that feedback connections must largely target inhibitory neurons. This is consistent with recent reports that top-down attention has a net-inhibitory effect on sensory cortex (Huang et al 2019; Yoo et al 2021) and with previous models predicting the need for feedback inhibition to sustain distributed persistent activity (Mejias and Wang 2021). A parsimonious explanation of the contrasting data on early sensory activity is that many tasks can be performed by maintaining a representation of only higher-order aspects of the stimuli, and therefore sustained activity is not required in early sensory cortex.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…To reproduce these latter experimental activity patterns, we found that feedback connections must largely target inhibitory neurons. This is consistent with recent reports that top-down attention has a net-inhibitory effect on sensory cortex (Huang et al 2019; Yoo et al 2021) and with previous models predicting the need for feedback inhibition to sustain distributed persistent activity (Mejias and Wang 2021). A parsimonious explanation of the contrasting data on early sensory activity is that many tasks can be performed by maintaining a representation of only higher-order aspects of the stimuli, and therefore sustained activity is not required in early sensory cortex.…”
Section: Discussionsupporting
confidence: 93%
“…Feedforward and feedback connections may also target different cell types. If both feedforward and feedback connections mainly target excitatory cells, models often fail to propagate activity, or display global network synchrony and instability (Joglekar et al 2018; Mejias and Wang 2021). This issue can be alleviated by assuming that feedback connections have a slight net bias towards targeting inhibitory cells in the so-called counterstream inhibition hypothesis (Mejias and Wang 2021).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations